Political Education–Occupy Wall Street’s First Year - DiSalvo, Jackie (Radical Teacher, 2013)
While Occupy Wall Street (OWS) is easily identified with direct action in the streets, equal recognition should be given to the vast amount of political education that took place. This article will give an overview of that and briefly assess its emphases and absences.